Cardiovascular disease prevention strategies for type 2 diabetes mellitus. (13th August 2017) - Katsiki, Niki; Purrello, Francesco; Tsioufis, Costas; Mikhailidis, Dimitri P.
ABSTRACT: Introduction : Type 2 diabetes mellitus (T2DM) is associated with several cardiovascular (CV) risk factors such as insulin resistance, obesity, hypertension, dyslipidaemia, non-alcoholic fatty liver disease as well as platelet and haemostatic abnormalities increasing the risk of thrombosis. Therefore, T2DM patients are at an increased risk for CV disease (CVD). Areas covered : This narrative review discusses the treatment of T2DM. This includes lifestyle measures (diet, exercise and smoking cessation) as well as hypolipidaemic, antihypertensive, weight reducing, antiplatelet and glucose lowering drugs. The focus is on the effects of these therapeutic strategies on CVD risk. Randomized controlled clinical trials (RCTs) reporting CVD outcomes with such drugs in T2DM patients are also reviewed. Expert opinion : Apart from current guidelines, the findings of RCTs on CVD outcomes in T2DM patients should be taken into consideration in daily clinical practice. Multiple risk factors should be targeted simultaneously in such high-risk patients in order to efficiently reduce the risk of CV events.